2008
DOI: 10.1007/s00125-008-1012-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired stroke volume and aerobic capacity in female adolescents with type 1 and type 2 diabetes mellitus

Abstract: Aim/hypothesis This study was designed to determine whether type 2 diabetic adolescents have reduced aerobic capacity and to investigate the role of cardiac output and arteriovenous oxygen difference (a−vO 2 ) in their exercise response. Methods Female adolescents (age 12-18 years) with type 2 diabetes mellitus (n=8) and type 1 diabetes mellitus (n=12) and obese (n=10) and non-obese (n=10) non-diabetic controls were recruited for this study. Baseline data included maximal aerobic capacity (cycle ergometer) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 10 publications
(15 reference statements)
6
98
0
2
Order By: Relevance
“…Another potential limitation was that the average maximal heart rate was lower in youth with type 2 diabetes relative to normoglycemic overweight controls which may explain group-wise differences in the primary outcome measure. Previous studies of cardiorespiratory fitness in youth with type 2 diabetes demonstrated similar reductions in maximal heart rate (35,39) and may be indicative of early central autonomic dysfunction (40). On average, however respiratory exchange ratios exceeded 1.10 in all groups and the rating of perceived exertion was >17/20 in all participants, suggesting that all youth attained volitional exhaustion and peak exercise.…”
Section: Limitationsmentioning
confidence: 53%
“…Another potential limitation was that the average maximal heart rate was lower in youth with type 2 diabetes relative to normoglycemic overweight controls which may explain group-wise differences in the primary outcome measure. Previous studies of cardiorespiratory fitness in youth with type 2 diabetes demonstrated similar reductions in maximal heart rate (35,39) and may be indicative of early central autonomic dysfunction (40). On average, however respiratory exchange ratios exceeded 1.10 in all groups and the rating of perceived exertion was >17/20 in all participants, suggesting that all youth attained volitional exhaustion and peak exercise.…”
Section: Limitationsmentioning
confidence: 53%
“…Among prepubertal boys with T1DM the participation in physical activity does not decrease compared to their healthy counterparts, while lower activity may be noted among girls [27]. However, in adolescence a decrease in physical activity may be noted both in girls and in boys with diabetes compared to their healthy peers [27,28]. These differences get bigger when the glycaemia levels are controlled less frequently [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…U chłopców z T1DM przed okresem pokwitania udział w AF nie zmniejsza się w stosunku do zdrowych rówieśników, natomiast u dziewcząt mogą występować spadki [27]. Ale już w wieku młodzieńczym odnotowuje się spadek AF zarówno u dziewcząt jak i chłopców w stosunku do ich zdrowych rówieśników [27,28]. Różnice pogłębiają się, gdy kontrola poziomu glikemii jest dokonywana z mniejszą częstotliwością [29,30].…”
Section: Discussionunclassified
“…Adults and adolescents with type 1 diabetes have reduced exercise capacity (8)(9)(10), which increases their risk for cardiovascular morbidity and mortality (11). The causes for this reduced exercise capacity are unclear.…”
mentioning
confidence: 99%
“…The causes for this reduced exercise capacity are unclear. However, recent studies have shown that adolescents with type 1 diabetes have lower stroke volume during exercise, which has been attributed to alterations in left ventricular function (9,10). Reduced left ventricular compliance resulting in an inability to fill the left ventricle appropriately during exercise has been shown to contribute to the lower stroke volume during exercise in both adults and adolescents with type 1 diabetes (12).…”
mentioning
confidence: 99%